Circadian Rhythm Effect in Depression Management: A Psychosocial Approach - Rifka Wangiana Yulia Putri (HM Publisher, 2023)
Depression is a kind of mental disorder. It is a risk factor for many diseases. Recently, it has been suggested to contribute to the high mortality rate, especially for young-middle ages. The incidence of depression is studied to be associated with sleep-style change that leads to internal circadian rhythm disruption. The circadian rhythm is related to the light-dark cycle of the sun. Dusk and dawn twilight are an important part of internal circadian rhythm synchronization. These moments correlate with the praying time of Muslims. A socio-spiritual approach could be a potential treatment for depressive disorder. At praying time for Muslims, the synchronization process of circadian rhythm is happening so that, hopefully, circadian disruption will resolve. This review aims to understand the impact of circadian rhythm on depression and its potential for depression treatment in the future.